2017
DOI: 10.1007/s13402-017-0339-3
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of a cancer stem-like phenotype mediated by alpha-lipoic acid in human lung cancer cells through down-regulation of β-catenin and Oct-4

Abstract: Our data are indicative for a novel regulatory role and underlying mechanism of LA in the negative regulation of a CSC-like phenotype in non-small cell lung cancer-derived cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…It reduced the phenotype of lung CSCs such as anchorageindependent growth and three dimensional sphere formations by diminution of the cellular proteins β-catenin and Oct-4. This was achieved by affecting the amount of active (phosphorylated) Akt (74). Thus Oct-4 could be a potential and novel target for enhancing the treatment of lung cancer.…”
Section: Therapeutic Approaches With Lung Cscsmentioning
confidence: 99%
“…It reduced the phenotype of lung CSCs such as anchorageindependent growth and three dimensional sphere formations by diminution of the cellular proteins β-catenin and Oct-4. This was achieved by affecting the amount of active (phosphorylated) Akt (74). Thus Oct-4 could be a potential and novel target for enhancing the treatment of lung cancer.…”
Section: Therapeutic Approaches With Lung Cscsmentioning
confidence: 99%
“…When patients receive anti-cancer therapies most tumor cells are usually killed, but subpopulations of cancer cells that are resistant to the treatment may remain and give rise to relapse. This phenomenon is thought to be due to the presence of CSCs [ 29 31 ]. Therefore, we first performed a sphere formation assay to test the ability of the OE-19 cell line to form putative CSC-derived spheres.…”
Section: Resultsmentioning
confidence: 99%
“…Certain members of the homeobox superfamily have been implicated in normal development as well as in the pathological development of cancer. OCT-4 is a homeobox gene well known for its function in generating induced pluripotent stem cells (Bhartiya, 2013;Seiler et al, 2011); this gene has also been identified as an oncogene known for promoting the features of cancer stem cells (Li et al, 2017;Phiboonchaiyanan & Chanvorachote, 2017). In addition to OCT-4, an increasing body of evidence reveals that homeobox genes may participate in the promotion of various malignant phenotypes such as the proliferation, migration and invasion of cancers (Hirao et al, 2019;Miwa & Kanda, 2019;Rodini et al, 2012;Song et al, 2019).…”
Section: Discussionmentioning
confidence: 99%